Hubungan Religiusitas dan Sikap Guru dengan Perilaku Menyontek pada Siswa SMA Swasta Islam Al-Ulum Terpadu Medan - Abdul Karim; Abdul Munir; Hasanuddin Hasanuddin (Universitas Medan Area, 2021)
This study aims to determine the relationship between religiosity and teachers' attitudes with cheating behavior in students of SMA Swasta Islam Al-Ulum Terpadu Medan. This type of research uses a correlational quantitative approach with multiple linear regression data analysis techniques. Sampling was done with the Total Sampling technique from a total population of 107 students obtained after the screening process. This study uses scale instruments of religiosity, teacher attitudes and cheating behavior. The results showed that: a) there is a significant negative relationship between religiosity and cheating behavior in students, which is indicated by a correlation coefficient (rx1y) = - 0.485; p = 0.000 0.05; and the weight of the relationship contribution is 30%. b) there is a significant negative relationship between teacher attitudes and cheating behavior in students, where the value of the correlation coefficient (rx2y) = - 0.547; p = 0.000 0.05; and the weight of the relationship contribution is 23.5%. c) there is a significant negative relationship between religiosity and teacher attitudes with students' cheating behavior, which is indicated by a correlation coefficient (R) = - 0.569; p = - 0.000 0.05; Freg = 24.943, then it can be concluded that the variables of religiosity and teacher attitudes together or simultaneously are related to the variables of cheating behavior. Thus it is stated that the hypothesis proposed in this study is declared accepted.